Interesy narodowe Federacji Rosyjskiej w Syrii na tle rosyjskiej interwencji w 2015 roku - Skuczyński, Maciej (Przegląd Strategiczny, 2016)
On September 2015 Russian Federation began intervention in Syria acting on behalf of Bassâr al-’Assad against Islamic State and other rebels who are fighting against Syria Arab Republic. This decision had been influenced by Russia’s objective reasons as well by particular interests of its administration. The main aim o f this article is to analyze national interests regarding Russian Federation’s intervention in Syria which are defined by author as: survival o f the state, political autonomy, economic prosperity and sense o f self-esteem o f state-society complex. The author also discusses particular interests o f Russian administration which he considers as being in accordance with national interests. Threads mentioned in the article consists of: historic relations between states, economic interests, an impact o f the intervention on Russian internal and foreign policy, the seaport in Tartüs and Russian citizens in Syria.